2013
DOI: 10.4209/aaqr.2012.09.0234
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Spatial and Temporal Variability of PM10 Concentrations Using MODIS Aerosol Optical Thickness in the Pearl River Delta Region, China

Abstract: Characterizing spatial and temporal variations of PM pollution is critical for a thorough understanding of its formation, transport and accumulation in the atmosphere. In this study, Aerosol Optical Thickness (AOT) data retrieved from a Moderate Resolution Imaging Spectroradiometer (MODIS) were used to investigate the spatial and temporal variations of PM 10 (particles with aerodynamic diameters of less than 10 μm) pollution in the Pearl River Delta (PRD) region. Seasonal linear regression models between 1-km … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…Aerosol optical thickness (AOT), derived from satellite observations, is a dimensionless measure of aerosol abundance and atmospheric extinction of radiance over the entire air column. Previous researches have revealed a strong positive relationship between satellite-based measurements of AOT and ground-based measurements of particulate matters smaller than 2.5 μm and 10 μm in aerodynamic diameters (PM2.5 and PM10, respectively) [15][16][17][18][19][20][21][22][23][24][25]. A summary of linear AOT/PM relationships, intercepts and correlation coefficients in several previous studies is shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Aerosol optical thickness (AOT), derived from satellite observations, is a dimensionless measure of aerosol abundance and atmospheric extinction of radiance over the entire air column. Previous researches have revealed a strong positive relationship between satellite-based measurements of AOT and ground-based measurements of particulate matters smaller than 2.5 μm and 10 μm in aerodynamic diameters (PM2.5 and PM10, respectively) [15][16][17][18][19][20][21][22][23][24][25]. A summary of linear AOT/PM relationships, intercepts and correlation coefficients in several previous studies is shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric particulate matter (PM10 and PM2.5, with diameters less than 10 µm and 2.5 µm) is a mixture of solid or liquid particles suspended in the air, and is an important air pollutant in urban environments [1][2][3]. Epidemiological studies have shown that PM2.5/PM10 and an increase in respiratory symptoms, lung cancer mortality, and cardiovascular disease are closely related [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Satellite sensors characterize key aerosol properties, such as the aerosol optical thickness or depth (AOD) and the aerosol effective radius, by measuring light extinction in an atmospheric column. Specifically, AOD data produced from the Moderate resolution Imaging Spectroradiometer (MODIS, on board the NASA platform Terra and Aqua) has been widely applied to examine the seasonal and regional variability of trace gases and aerosol particles (Alpert et al, 2012;Indira et al, 2013;Lalitaporn et al, 2013;Zheng et al, 2013;Mehta, 2015), and to evaluate its relation to air pollution (Zhu et al, 2011) or significant emission sources, such as burning activities (Koren et al, 2007;Bevan et al, 2009;Vadrevu et al, 2011). In view of the important impacts on global climate and regional air quality, the scientific community has developed a number of operational fire products based on the detection of thermal anomalies (i.e., active fires, abbreviated to AF) and land surface changes (i.e., burned areas, abbreviated to BA).…”
Section: Introductionmentioning
confidence: 99%